2019
DOI: 10.3390/app9040688
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Linearization Methods for a Control System with Clutching Inerter Damper

Abstract: Inerter-based dampers have gained great popularity in structural vibration control. In this paper, equivalent linearization methods (ELMs) for a single-degree-of-freedom (SDOF) system with a clutching inerter damper (CID) are studied. The comparison of a SDOF system with a CID and an inertial mass damper (IMD) shows the advantage of the CID. Considering that the system with the CID is nonlinear, which is problematic for its performance evaluation and the integrated design of the structure and control system, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Compared with the inerter, the CID has better control for the displacement reduction of both the short-period structures and the long-period structures. Considering the inherent nonlinearity of the CID, several equivalent linearization methods have been developed in previous studies (Li et al, 2019; Wang and Sun, 2018).…”
Section: Establishment Of Ctmd Modelmentioning
confidence: 99%
“…Compared with the inerter, the CID has better control for the displacement reduction of both the short-period structures and the long-period structures. Considering the inherent nonlinearity of the CID, several equivalent linearization methods have been developed in previous studies (Li et al, 2019; Wang and Sun, 2018).…”
Section: Establishment Of Ctmd Modelmentioning
confidence: 99%
“…The clutch can prevent the inerter from pushing the structure to move when the structural velocity begins to reduce, which mitigates the response of the structure further compared with the rotational inerter. Previous study by the authors has indicated that the CID can be regarded as a combination of an inerter and a viscous damper for a single degree‐of‐freedom (DOF) system …”
Section: Introductionmentioning
confidence: 99%
“…Previous study by the authors has indicated that the CID can be regarded as a combination of an inerter and a viscous damper for a single degree-of-freedom (DOF) system. 9 Many inerter-based devices have been proposed in the field of vibration control. [10][11][12][13][14] Ikago et al 11 proposed a novel device called tuned viscous mass damper reformed by a supplemental oscillator and the viscous mass damper, of which the superiority has been verified by analytical results and the shaking table test.…”
Section: Introductionmentioning
confidence: 99%
“…In this special issue, both modeling and applications related to inerter dampers are addressed. On the modeling side, new equivalent linearization methods for a control system with a clutching inerter damper are developed [25], and on the application side, the inerter dampers are applied to the vibration control of suspended structures [26] and cables [27]. The inerter dampers are effective in reducing structural vibrations.…”
mentioning
confidence: 99%
“…In summary, the topics in the special issue include new damping materials development [37], new damper vibration modeling, novel algorithms for active vibration control [44,45], novel passive damping methods and devices [25][26][27][28][29][30], innovative energy dissipation devices [38][39][40], and an explorative characterization of materials for energy dissipation [33], among others. For the future trends of research in energy dissipation for vibration control, two avenues should be noted.…”
mentioning
confidence: 99%